The oddities and wonders in the Kurdish folk tale, the book of: “Narina gulbarin and some of the oral folk tales as a model” - Abdulrahman, Shivan; Saleh, Mohsin (Humanities Journal of University of Zakho, 2023)
Oddities and wonders are widley found in the Kurdish folklore tales, and this matter is due to the imagination of the narrator of the folklore tales. The presence of oddities and wonders in the events of the story becomes a factor in narrating the events one after the other, and at the same time it is conveyed in an interesting and exciting way reaches the reader and listener and adds a supernatural dimension or transcends nature to the story. Is it true that the miraculous is that violent and hidden interference that interferes with the reality of daily life, or more precisely, creates isolation or a rift in the prevailing and familiar system of man? Therefore, such a study was conducted on the Kurdish folkloric tale under the title Oddities and wonders in the Kurdish folkloric tale “Narina Gulbarin” and oral tales as a model, and it is an attempt to show the side of the strangeness and wonders in the tale and how to use it. This study consists of two parts: the first part deals with the theoretical background, and the second part is devoted to the practical part.